2018
DOI: 10.1136/bmjopen-2018-022678
|View full text |Cite
|
Sign up to set email alerts
|

Risk of olfactory dysfunction of the workers in the automobile repair, printing, shoemaking and plating industries in Korea: a cross-sectional study

Abstract: ObjectivesThe present study was performed to investigate the prevalence of olfactory dysfunction in workers exposed to hazardous substances in a variety of occupations in Korea.MethodsWe designed a cross-sectional study. The exposed group (n=296) consisted of Korean workers in the automobile repair, printing, shoemaking and plating industries and was compared with office workers (non-exposed group, n=99). A self-report questionnaire was administered to the subjects for demographic characteristics. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Consistently, a previous study examined taste and smell functions based on objective measures and found severe taste dysfunction had higher prevalence than severe smell dysfunction among older adults [37]. In addition, when compared with the results from Lee et al [31], we observed a smaller effect size of cadmium exposure. The difference might have been caused by differences in (1) the study population-we used a nationally representative population in this study, while a high-risk population (i.e., workers from certain types of industries) was targeted by Lee et al [31]-and (2) the exposure measurement-cadmium was assessed using blood samples in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistently, a previous study examined taste and smell functions based on objective measures and found severe taste dysfunction had higher prevalence than severe smell dysfunction among older adults [37]. In addition, when compared with the results from Lee et al [31], we observed a smaller effect size of cadmium exposure. The difference might have been caused by differences in (1) the study population-we used a nationally representative population in this study, while a high-risk population (i.e., workers from certain types of industries) was targeted by Lee et al [31]-and (2) the exposure measurement-cadmium was assessed using blood samples in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Although declines in cadmium exposure among teens and adults were observed in prior studies, long-term exposure to low levels of cadmium still poses risks of adverse outcomes to the general population [30]. Lee et al [31] designed a cross-sectional study to investigate the risk of smell dysfunction in workers with occupational exposure to heavy metals such as cadmium and lead in Korea. Workers who were exposed to occupational pollutants were observed to have higher prevalence of smell dysfunction than those who were not.…”
Section: Introductionmentioning
confidence: 99%
“…The job might be a risk factor for acquiring olfactory disorders. Lee et al [24] from Korea reported a higher prevalence rate of olfactory disorders in certain jobs, automobile repair (45.1%), printing (69.7%), and shoemaking and plating (88.9%) workers in comparison to the o ces' workers (21.2%). It is wellknown that there is no one immune against the COVID-19 disease, but healthcare workers are more vulnerable [25].…”
Section: Discussionmentioning
confidence: 97%
“…The job might be a risk factor for acquiring olfactory disorders. Lee et al [ 24 ] from Korea reported a higher prevalence rate of olfactory disorders in certain jobs, automobile repair (45.1%), printing (69.7%), and shoemaking and plating (88.9%) workers in comparison to the offices' workers (21.2%). It is well-known that there is no one immune against the COVID-19 disease, but healthcare workers are more vulnerable [ 25 ].…”
Section: Discussionmentioning
confidence: 99%